Review of currently used standardized measures of quality of life after ventral incisional hernia repair: systematic review - Majeed, Talal; Chauhan, Mohammad Noor (International Surgery Journal, 2019)
After advancements in surgical and anaesthetics expertise and increased life spans among patients with complex abdominal surgeries, clinicians are left with the next main challenge, to how to improve the quality of life in patients with incisional hernia resulted from previous complex abdominal surgeries. To date there is no consensus over the choice of instrument and time frame for its administration in the literature. The aim of this review was to search for the current literature on measurement of quality of life in patients with ventral incisional hernia repair and to explore how effective each QOL instrument was for measuring impact on quality of life after ventral incisional hernia repair. In accordance with PRISMA guidelines two independent clinicians searched for Mesh and specific terms related to quality of life in patients with ventral incisional hernia. Search was made on PubMed, Embase and other research databases. Trial registries were searched for any published or unpublished trials. Literature search came up with 461 articles. After scanning and removal of duplication, 200 articles were subjected to inclusion and exclusion criterion and 59 articles were selected for qualitative analysis. Different scales for the measurement of quality of life after ventral incisional hernia repair were found. The incidence of incisional hernia itself was found to be the biggest determinant of poor quality of life, regardless of timescale of follow up and type of surgery performed. No single instrument was found to be complete enough to address the wide-ranging health-related quality of life issues in patients after incisional hernia repair.